Understanding the Impact of Intimate Partner Violence Type and Timing on Pre-exposure Prophylaxis Knowledge, Acceptability, Sexual Behavior, and Gender Roles Among Women of Color - Villalba, Karina (Journal of interpersonal violence, 2022)
Knowledge and acceptability are key factors for pre-exposure prophylaxis (PrEP) use among women with a history of intimate partner violence (IPV) and research suggests that different types of IPV affect PrEP uptake differently. Few studies have examined whether the type (i.e., physical, sexual, and psychological) and timing (i.e., lifetime, past year) of IPV experiences are related to PrEP knowledge and acceptability, or whether gender roles and sexual risk behaviors affect PrEP use. We aimed to examine the associations between lifetime and past-year physical, sexual, and psychological IPV experiences on PrEP-related outcomes (i.e., knowledge, acceptability, sexual behavior if on PrEP) and the association between gender roles and PrEP-related outcomes. A total of 186 women of color at risk for HIV participated in this study, of whom 54% had ever experienced partner violence. Results showed that lifetime psychological (OR 3.0, 95% CI 1.1?9.4) and lifetime physical IPV (OR 5.5, 95% CI 1.2?18.9) were significantly associated with increased PrEP knowledge. lifetime psychological (OR 6.3, 95% CI 1.0?13.6) and lifetime physical IPV (OR 4.3, 95% CI 4.3?11.5) were significantly associated with increased sexual behavior if on PrEP. Past year physical IPV was significantly associated with interest in using PrEP (OR 1.9, 95% CI 1.7?4.3) and with sexual behavior if on PrEP (OR 4.0, 95% CI 1.1?13.1). Being subordinate to others was also significantly associated with interest in using PrEP (OR 1.5, 95% CI 1.2?2.4) Self-silencing was significantly associated with increased sexual behavior if on PrEP (OR 1.2, 95% CI 1.0?1.5). Gender norms and IPV type and timing can influence whether a person is interested in PrEP use. Both lifetime and past-year IPV experiences need to be examined in the context of gender norms when prescribing PrEP to encourage uptake and continuation among vulnerable women at risk for HIV.